The Effects of osteoanabolic exercises on bone mineral density of osteoporotic females: A randomized controlled trial - Khan, Amna Aamr; Farhad, Ali; Siddiqui, Pirzada Qasim Raza; Ansari, Basit (International Journal of Health Sciences, 2018)
Objectives: With the increase in the life expectancy of older adults, the scoring diagnosis of osteoporosis has been highly reported hence rising the incidence of fragility fractures due to decrease in bone mineral density (BMD), thereby significantly impacting the quality of life and health status of elderly population. The aim of this study is to identify the impact of different exercise regimes in improving the BMD among osteoporotic females. Methodology: A trial was conducted on 93 diagnosed postmenopausal osteoporotic females aged 50–75 years screened on the basis of physical activity readinessquestionnaire and YOU form randomly divided equally into three groups’, that is, aerobic, anaerobic, and osteoanabolic exercises using an envelope method. The intervention was given on the basis of American College of Sports Medicine (ACSM), frequency, intensity, time, and type protocol for the period of 12 weeks. The pre- and post-BMD was determined to find out the improvements on the t-value of the participants. The outcome measure was calculated using a peripheral dual X-ray absorptiometry scan (bone densitometer). Results: At 95% of confidence interval, the pre- and post-median difference observed within the osteoanabolic group was 0.4 followed by 0.3 and 0.1 in the aerobic and anaerobic groups, respectively. The level of significance was determined by applying the Friedman test revealing a statistically significant difference P < 0.001 between the groups. Further, post hoc analysis shows that osteoanabolic exercises were more significant in comparison with aerobic and anaerobic exercises. Conclusion: Structured physical exercises based on ACSM protocol show improvement among the osteoporotic females; however, the impact of osteoanabolic exercises significantly increased the BMD, thus reducing the t-value. However, larger scale studies in different clinical settings are recommended for more accurate results.